A Novel Space Large Deployable Paraboloid Structure with Power and Communication Integration - Tao Zheng; Zheng Fei; Xi Rui; Lide Yan (International Journal of Antennas and Propagation)
The combination of a solar array and a communication antenna can reduce the entire mass, physical size, and cost in space applications. Currently, related studies mainly focus on the combination of the two structures on the one flat plate structure (FPS). Compared with the FPS, a paraboloid structure has a lower surface density and higher conversion efficiency. Therefore, a novel space large deployable paraboloid structure with power and communication integration (SSPCI) is proposed and designed in detail, for spacecraft on a sun synchronous earth orbit; it consists of a cable mesh membrane reflector (CMMR), an energy conversion device (ECD), and a three-extensible-rod (TER) pointing mechanism. To achieve the goal of integrating power and communication, the TER pointing mechanism drives the CMMR/ECD to track the sun in the sunshine region or to turn to face the ground station/other target in the Earth’s shadow region. Then, through simulation analyses of the deploying process, static force at a limit orientation, and sun tracking process of the SSPCI, it is proved that the SSPCI is feasible and has satisfactory performance. Finally, deploying experiments of the folded hoop of the CMMR and sun tracking experiments of the TER pointing mechanism on the ground were carried out successfully, which proves that the folded hoop can be deployed successfully with fairly high deploying dependability, and the TER pointing mechanism is feasible for the SSPCI from the mechanism principle and the control mode in space applications indirectly. Moreover, the tracking accuracy of the TER pointing mechanism is estimated to be within ±0.4° although the machining precision of its components is not high.